Comparative efficacy and safety of tigecycline vs colistin for Carbapenem-resistant Enterobacteriaceae (CRE) infections in cancer patients - Sai Vaibhavi Gumudavelli; Akshay Shelke; Pallavi Priya; Richa Chauhan; Sameer Dhingra (Clinical Epidemiology and Global Health)
Background: Carbapenem-resistant Enterobacteriaceae (CRE) infections pose a significant threat owing to their high mortality rates and limited treatment options, exacerbated by antibiotic misuse and the spread of resistance genes. Objective: This study aimed to compare the effectiveness, safety, and outcomes of tigecycline and colistin in the treatment of CRE infections in cancer patients. Methods: A 9-month prospective observational study was conducted at a tertiary-care cancer hospital in Bihar, India. The study included 150 patients with CRE infections divided into tigecycline (n = 90) and colistin (n = 60) groups. Results: Patients receiving tigecycline had higher levels of direct bilirubin, alkaline phosphatase, and creatinine. However, tigecycline was associated with shorter hospital stays (13.73 vs 17.45 days, p = 0.016) and therapy durations (5.7 vs 7.3 days, p = 0.04). Infection recurrence rates (3.3 % vs. 5 %) and 30-day mortality rates (17.6 % vs. 18.9 %, p = 0.663) were similar between the two groups. Conclusion: Both tigecycline and colistin were effective in treating CRE infections in patients with cancer. Although tigecycline was associated with improved hospital stay and therapy duration, it also showed potential liver and kidney function adverse effects. These findings highlight the need for careful consideration of treatment options for CRE infections in patients with cancer.